Bio-Fabricated Silver Nanoparticles from the Leaf Extract of the Poisonous Plant, Holigarna arnottiana: Assessment of Antimicrobial, Antimitotic, Anticancer, and Radical-Scavenging Properties - Anthyalam Parambil Ajaykumar; Ovungal Sabira; Valiyaparambil Sivadasan Binitha; Sudhir Rama Varma; Anjaly Mathew; Kodangattil Narayanan Jayaraj; Pandikkadan Ayyappan Janish; Koladath Vasu Zeena; Padannappurath Sheena; Veena Venugopal; Priyanka Palakkapparambil; Aswathi (MDPI AG, 2023)
This study presents a novel approach to fabricate silver nanoparticles (AgNPs) using the poisonous plant, Holigarna arnottiana leaf extract. The formation of AgNPs was confirmed by a color change from green to dark brown and validated by UV analysis. FTIR analysis identified functional groups on the AgNPs, while Zeta potential analysis assessed their stability. TEM analysis established an average diameter of 18 nm and a spherical morphology for the nanoparticles. LC MS analysis coupled with database searches revealed the presence of diverse bioactive compounds, including flavonoids, nucleotides, dipeptides, enzymes, and glycosides. These compounds are postulated to act as reducing agents in the leaf extract-mediated synthesis process. Moreover, the bio-fabricated AgNPs exhibited noteworthy anticancer properties against DLA cells. In addition, AgNPs displayed substantial antimitotic effects in an assay involving Allium cepa root cells. These findings underscore the potential of the AgNPs as cytotoxic agents. The biosynthesized AgNPs showed antimicrobial activity against various bacterial pathogens, including Escherichia coli, Klebsiella pneumoniae, and Staphylococcus aureus. Furthermore, the AgNPs exhibited outstanding radical-scavenging properties in the DPPH assay, suggesting their potential application in antioxidant therapies. The study collectively highlights the successful synthesis of AgNPs through a green, biocompatible approach, and demonstrates their promising potential for anticancer, antimitotic, and radical-scavenging applications.